2016
DOI: 10.1007/s12010-016-2155-z
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Biosynthesis of Polyhydroxyalkanoates and Extracellular Polymeric Substance (EPS) from Crude Glycerol from Biodiesel Production by Different Bacterial Strains

Abstract: Simultaneous synthesis of polyhydroxyalkanoates (PHAs) and polyglutamic acid (PGA) was investigated in cultures of Cupriavidus necator IPT 026, C. necator IPT 027, C. necator IPT 029, and Bacillus megaterium INCQS 425 strains in a medium containing 2.0 % sucrose or crude glycerol from biodiesel (CGB), in an orbital shaker (35 °C, 180 rpm, 72 h). All the strains tested simultaneously produced PHA and PGA in a medium containing CGB. The C. necator IPT026 culture provided higher molecular mass PHA and PGA (1128.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 51 publications
3
13
0
2
Order By: Relevance
“…The biomass from PHA producer strains were subjected to FTIR spectroscopy and for all the strains the peaks were obtained at about 1600 absorbance in both the PHA detection agar supplemented with 2% glucose and 2 % coconut oil as carbon source. The absorbance at these peaks confirms the presence of carboxylic groups, which indicates potential of these strains for bio-plastic production (de Jesus- Assis et al, 2016). The bacterial strains studied in this work are not very well studied, but they have shown promising results for the production of bio-plastic and utilization of lipid carbon source, it has been observed that not a large number of bacteria are able to cleave the ester linkages in the lipids, if a bacterium can break a linkage than it can get a large amount of carbon which is not possible with monosaccharaides or simple disaccharides.…”
Section: O N L I N E F I R S T a R T I C L Ementioning
confidence: 86%
“…The biomass from PHA producer strains were subjected to FTIR spectroscopy and for all the strains the peaks were obtained at about 1600 absorbance in both the PHA detection agar supplemented with 2% glucose and 2 % coconut oil as carbon source. The absorbance at these peaks confirms the presence of carboxylic groups, which indicates potential of these strains for bio-plastic production (de Jesus- Assis et al, 2016). The bacterial strains studied in this work are not very well studied, but they have shown promising results for the production of bio-plastic and utilization of lipid carbon source, it has been observed that not a large number of bacteria are able to cleave the ester linkages in the lipids, if a bacterium can break a linkage than it can get a large amount of carbon which is not possible with monosaccharaides or simple disaccharides.…”
Section: O N L I N E F I R S T a R T I C L Ementioning
confidence: 86%
“…MA03 achieved a considerable amount of intracellular biopolymer (63.6% cell dry weight [CDW]) and final PHB production was 2.9 g L −1 from 2% crude glycerol after 72 hours of cultivation . Zobellella denitrificans utilized crude glycerol (2%) to produce PHA with yield up to 2.82 g L −1 , and those were around fourfold that compared with the amount of PHA produced by Bacillus megaterium INCQS 425 and Cupriavidus necator IPT 027 of 0.78 and 0.33 g L −1 , respectively …”
Section: Discussionmentioning
confidence: 97%
“…77 Zobellella denitrificans utilized crude glycerol (2%) to produce PHA with yield up to 2.82 g L −1 , and those were around fourfold that compared with the amount of PHA produced by Bacillus megaterium INCQS 425 and Cupriavidus necator IPT 027 of 0.78 and 0.33 g L −1 , respectively. 86 Different concentrations of crude glycerol were used for production of PHA by Bacillus thuringiensis EGU45, whereas the accumulation of PHA inside the bacterial cells increased from 1540 to 3585 mg L −1 by raising the crude glycerol input from 1% to 5%. Meanwhile, the high concentration of crude glycerol (10%) slightly inhibited the production of PHA of 2625 mg L −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Para começar, o glicerol bruto é gerado como um co-produto na produção de biodiesel, e por cada 10 galões de biodiesel produzido, 1 galão de glicerol bruto é gerado (NARANJO et al, 2013a). Estima-se que até 2016, a produção mundial de biodiesel deve chegar aos 37 bilhões de galões, o que implica uma produção aproximada de 4 bilhões de galões de glicerol bruto (DE JESUS ASSIS et al, 2016b). No Brasil, a mistura de 7% de biodiesel com diesel tornou-se obrigatória em 2014, portanto, a quantidade de biodiesel produzido no Brasil aumentou 241% nos últimos cinco anos, atingindo 9 milhões de galões em 2014 (FABER; FERREIRA-LEITÃO, 2016), sendo este produzido principalmente a partir de soja (ANDRÉ CREMONEZ et al, 2015).…”
Section: Seleção Produção E Determinação De Phaunclassified
“…O custo total de produção de PHB depende do microrganismo (rendimento e produtividade), as fontes de carbono e de nitrogênio (substratos), as condições de fermentação (temperatura, aeração, pH) e os processos de recuperação e purificação(NARANJO et al, 2013b;PRADOS;MAICAS, 2016).Finalmente, os polímeros de PHA podem ser sintetizados por algumas espécies halófilas dos géneros Haloferax,Halococcus, Natronobacterium, Natronococcus, Bacillus, Cupriavidus, Staphylococcus, Micrococcus, Methylobacterium, Paracoccus e Rhodococcus. Dependendo do género, alguns destes microrganismos são capazes de sintetizar, além de PHA, exopolissacarídeos (EPS)(DE JESUS ASSIS et al, 2016a).…”
unclassified